The efficacy of topical prostaglandin analogs for hair loss: A systematic review and meta-analysis - Jiang, Shangxuan; Hao, Zhuolun; Qi, Wenli; Wang, Zhenxing; Zhou, Muran; Guo, Nengqiang (Frontiers in Medicine, 2023)
Background Prostaglandin analogs have been found to have more versatile uses: treatment of open-angle glaucoma, high intraocular pressure, vitiligo, and other treatments. And prostaglandin analogs have been found to have an important role in the hair growth cycle. However, prostaglandin analogs have not been sufficiently studied for hair (including hair, eyelashes, and eyebrows) regeneration. In this study, a systematic review and meta-analysis of topical prostaglandin analogs on hair loss was performed. Objective The purpose of this meta-analysis is to determine the efficacy and safety of topical prostaglandin analogs for treating hair loss. Methods We searched PubMed, Embase, and Cochrane Library databases comprehensively. Data were pooled using Review Manager 5.4.1, and subgroup analyses were performed if necessary. Results There were six randomized controlled trials included in this meta-analysis. All studies compared prostaglandin analogs with placebo, and one trial consisted of two sets of data. The results showed that prostaglandin analogs could significantly improve the hair length and density (p < 0.001). As far as adverse events are concerned, there was no significant difference between the experimental group and the control group. Conclusion In patients with hair loss, the topical prostaglandin analogs have better therapeutic efficacy and safety than placebo. However, the best dose and frequency of experimental treatment require further studies.